#TITLE_ALTERNATIVE# - ROSYIDAH (NIM 30504010), AFIFAH
The Aurivillius oxides family, with general formula of [Bi2O2][An-1BnO3n+1], can be described as the combination of regular stacking between the [Bi2O2]2+ slabs and perovskite-like [An-1BnO3n+1]2- blocks. These oxide materials have been investigated widely due to their potential applications in ferroelectric random access memories (FRAM). Systematic investigation of these structures at room temperature and their transition at high temperature have been carried out. Cation substitution has also been carried out both in [Bi2O2]2+ or perovskite blocks. The substitution produced Aurivillius oxide defects and could induce change in the physical-chemistry properties. The aim of the work is to investigate the chemistry defect on 2-5 layer Aurivillius oxides. Specifically to obtain: the stability of defect in Aurivillius oxides, both in [Bi2O2]2+ sheets and perovskite-like blocks with isovalent or aliovalent dopants; new defect Aurivillius oxides, which have ferroelectric properties; and correlation of defect and ferroelectric properties. The atomic simulation techniques of 2-5 layer representative Aurivillius oxides which are based on energy minimisation procedures and embodied in the General Utility Lattice Program (GULP) code were used in this study. A number of the predicted stable composition were then synthesized by the solid state reaction method at atmosphere pressure. The obtained oxides were characterized using highresolution powder X-ray diffractometer. Effect of the defect on physical properties, especially ferroelectric properties, were measured using RT 66A Ferroelectric System-Radiant Technology. The simulation results show that atomic simulation can acurately reproduce the experimental data and thus provide a valid starting point for the defect calculations. On the simulation of defect oxides, calculations were performed to obtained the energies of isolated vacancy defects in various atomic position of Bi3TiNbO9, Bi4Ti3O12, BaBi4Ti4O15 and Ba2Bi4Ti5O18. The results suggested that oxygen vacancies are in sites close to bismuth ion, which are 'over-bonded', and vacancy formation at this site would help to reduce the inherent stress in the lattice within those layer. These oxygen vacancy defects are the predominant factor of fatiguefree reduction on ferroelectric materials. The calculation of defect energies at Bi3TiNbO9, Bi4Ti3O12, BaBi4Ti4O15 and Ba2Bi4Ti5O18 with Pb2+, Al3+, Ga3+, In3+ and Ta5+ dopants show that iso-valent or alio-valent could substitute at both Bi and Ti sites. Trivalen (Al3+, Ga3+, In3+) dopants and Pb2+ were found more favourably at Bi site, and Ta5+ at Ti site. Dopant of Al3+, Ga3+, In3+ and Pb2+ were found to be more stable in Bi3+. The equivalence of their charge is believed to enabling the substitutions. The Pb2+, which is isoelectronic with Bi3+ cation, [Xe] 4f14 5d10 6s2, and the presence of 6s2 lone pair electrons responsible for its stability at Bi site. Substitution of Ta5+ dopant on perovskite Ti(1) site is due to their similar ionic radii, 0.64 Armstrong and 0.605 Armstrong for Ta5+ and Ti4+ respectively. The two layer Aurivillius oxides: Bi2.95A0.05TiNbO9 and Bi3Ti0.95Ta0.05NbO9, three layer Aurivillius oxides: Bi3.95A0.05Ti3O12 and Bi4Ti2.95Ta0.05O12, four layer Aurivillius oxides: BaBi3.95A0.05Ti4O15 and BaBi4Ti3.95Ta0.05O15, five layer Aurivillius oxides: Ba2Bi3.95A0.05Ti5O18 and Ba2Bi4Ti4.95Ta0.05O18 with A = Pb, Al, Ga, In; have been synthesized by the solid state reaction method. The powder X-ray diffraction patterns of all composition suggested that these powders were single phase compounds without impurity. Structural parameters of the obtained Aurivillius oxides were refined using the Rietveld method embodied in the Rietica program. All obtained oxides still adopt Aurivillius structures, as their parent oxides. Ferroelectric properties were determined using pressed ceramics. The hysteresis loops of the obtained 2-5 layer Aurivillius oxides showed the typical ferroelectrics loops. The higher the dopant valention the higher the measured spontaneous polarisation. The spontaneous polarization calculated from the ideal tetragonal positions showed that the defect oxides have higher polarization than their respective parents compounds, in agreement with the measurements.